Efficient carbon-based catalytic electrode as well as preparation method and application thereof
By dispersing copper metal salts on carbon-based single-atom catalytic electrodes, forming a Cu-N4 coordination structure, and using electron transfer mechanism to degrade organic matter, the existing catalytic electrodes have been solved, and the efficient and selective water treatment effect is achieved.
Patent Information
- Application Number
- CN202510183734.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-02-19
AI Technical Summary
The existing catalytic electrodes have low reaction efficiency in water treatment, are susceptible to coexistence of ions in water, and are difficult to selectively remove organic pollutants.
A carbon-based single-atom catalytic electrode is used to stably disperse the copper metal salt on the carbon nanotubes to form a Cu-N4 coordination structure, and the electron transfer mechanism is used to degrade organic matter and avoid the formation of free radicals.
The catalytic reaction rate and selectivity are improved, the adaptability to complex water quality is enhanced, the secondary pollution of water bodies is reduced, and the efficient removal of difficult-to-degrade organic pollutants is achieved.
Smart Images

Figure CN119858963A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalytic technology, and in particular to a high-efficiency carbon-based catalytic electrode and a preparation method and application thereof. Background Art
[0002] In recent decades, a variety of new chemicals have been designed, produced and widely used to meet the needs of rapid urbanization and industrialization in modern society. These chemicals may pollute aquatic systems during production, use or disposal. Currently, a variety of new chemicals have been detected in aquatic systems (rivers, lakes and oceans, etc.). However, some organic compounds (such as antibiotics, microplastics, artificial sweeteners, etc.) pose a potential threat to biota and human health due to their non-biodegradability, persistence and toxicity in nature. Physical treatment methods, such as membrane filtration, can remove such substances through steric exclusion, but this method cannot achieve harmless degradation. Biological treatment methods can use microorganisms to oxidize and decompose organic matter in wastewater and convert it into stable and harmless substances. However, such methods are usually inefficient, complicated to operate, and unstable in effect. Chemical treatment is a wastewater treatment method that separates, removes organic pollutants in wastewater and converts them into harmless substances through chemical reactions and mass transfer. Among them, the electrochemical method is one of the most effective wastewater treatment technologies. It can not only induce the production of highly active oxidative species (free radicals, etc.) through catalytic electrodes, directly degrade or mineralize difficult-to-degrade and toxic organic pollutants into harmless products, but also degrade organic matter through non-free radical pathways such as electron transfer and singlet oxygen. The electrochemical method of degrading organic pollutants in water avoids the addition of powder catalysts through the design of catalytic electrodes, which greatly solves the problem of difficult recovery of powder catalysts.
[0003] However, water treatment processes based on free radical mechanisms are easily interfered by coexisting inorganic ions in water and cannot selectively remove organic pollutants in water. Therefore, water treatment processes based on electron transfer pathways have gradually attracted attention. This pathway achieves rapid degradation of pollutants through the directional migration of pollutant electrons, is less interfered by coexisting substances in water, and has strong selectivity for electron-rich pollutants. It is one of the effective means to deal with organic pollution problems in complex water quality.
[0004] In addition, in the existing catalytic electrode system, the reaction efficiency still has a lot of room for improvement due to the influence of the electrode's own properties. For example, the electrode material itself may have defects, such as lattice defects, dislocations, vacancies, etc. These defects will affect the electron transport and ion diffusion of the material, and then affect the rate and selectivity of the catalytic reaction. Carbon-based single-atom catalytic electrodes have attracted attention in the field of electrochemical water treatment due to their high metal atom utilization and high efficiency. Therefore, it is necessary to develop an efficient carbon-based single-atom catalytic electrode based on an electron transfer mechanism, which can improve the electrode activity and reaction rate while overcoming the defects of traditional catalytic electrodes, efficiently remove difficult-to-degrade organic pollutants in water, expand the application of carbon-based catalytic electrodes in sewage treatment, and achieve the purpose of green and pollution-free protection of the water environment. Summary of the invention
[0005] The purpose of the present invention is to provide a high-efficiency carbon-based catalytic electrode and a preparation method and application thereof. The electrode prepared by the present invention can be used for electrochemical oxidation to efficiently remove difficult-to-degrade organic pollutants in water, thereby achieving the purpose of efficient and green protection of the water environment.
[0006] The technical solution adopted by the present invention is: a method for preparing a high-efficiency carbon-based catalytic electrode, wherein the electrode is based on carbon felt, and a carbon nanotube single-atom catalyst precursor is stably and evenly dispersed on the electrode surface through adhesion.
[0007] A method for preparing a high-efficiency carbon-based catalytic electrode comprises the following steps:
[0008] 1) dissolving carbon nanotubes (CNTs), polyvinyl pyrrolidone (PVP) and copper metal salt (such as copper chloride CuCl2·2H2O) in ethanol, stirring to make the mixture uniform and heating to volatilize the ethanol;
[0009] 2) After the ethanol is completely evaporated, the mixture is placed in a tube furnace and heat-treated in a nitrogen atmosphere. After cooling, the mixture is treated with a dilute acid solution, and then washed with deionized water until the washing water is neutral. After drying, a single-atom catalyst precursor Cu-CNTs based on carbon nanotubes is obtained.
[0010] 3) The carbon nanotube single atom catalyst precursor is dispersed in a solvent with a volume ratio of 1:1 between water and ethanol, and an adhesive is added thereto, and ultrasonication is performed to make the precursor dispersed uniformly, and the precursor is then coated on a conductive graphite felt and dried.
[0011] 4) The obtained electrode can not only be used in the field of sewage treatment to degrade difficult-to-degrade organic pollutants in water, but can also be used for other electrocatalytic reactions.
[0012] Further, the copper metal salt in step 1) is copper chloride, copper nitrate or copper sulfate. The ratio of the copper metal salt (such as copper chloride CuCl2·2H2O) to carbon nanotubes (CNTs) is 1:12-5:12, and most preferably, the mass ratio of carbon nanotubes to copper metal salt is 6:1. The mass ratio of the copper metal salt (such as copper chloride CuCl2·2H2O) to polyvinyl pyrrolidone (PVP) is 1:24-5:24. Most preferably, the mass ratio of the copper metal salt to polyvinyl pyrrolidone is 1:12.
[0013] Furthermore, in step 1), the mixing heating temperature is 60-80 degrees Celsius, and after the ethanol is completely volatilized, the remaining mixture is collected.
[0014] Furthermore, in step 2), the pyrolysis temperature is 600-900 degrees Celsius, preferably 900 degrees Celsius, and the heating rate is 2-10 degrees Celsius / minute, preferably 3 degrees Celsius / minute.
[0015] Furthermore, in step 2), the pyrolysis time is 1.5-4 hours, preferably 2 hours.
[0016] Furthermore, in step 2), the dilute acid solution is 0.5-1.5 mol / L dilute sulfuric acid or 0.5-1.5 mol / L dilute hydrochloric acid, and most preferably, the dilute acid solution is 1 mol / L dilute sulfuric acid or 1 mol / L dilute hydrochloric acid, the washing time is 2-4 hours, and then centrifuged with deionized water to wash until the pH of the washing solution is 6-8.
[0017] Furthermore, in step 3), the adhesive is Nafion 117 solution, chitosan or resin (such as conductive adhesive), preferably Nafion 117 solution.
[0018] Further, in step 3), the coating amount is 0-5 mg / m 2 , preferably 1 mg / m 2 .
[0019] Further, in step 3), the carbon felt substrate is conductive graphite felt, carbon cloth, carbon paper, titanium felt or copper felt, the carbon felt substrate can be replaced by carbon cloth, carbon paper, titanium felt and copper felt, etc., the conductive carbon felt can be replaced by carbon paper and titanium felt, and Cu-CNTs@CF and Cu-CNTs@TiF are obtained respectively, with a loading of 0-20 mg / m 2 .
[0020] Furthermore, the Cu atoms and N atoms in the electrode form a Cu-N4 coordination, and the copper atoms and nitrogen atoms in the carbon-based catalytic electrode prepared by the method form a Cu-N4 coordination structure, which is distributed on the electrode surface in the form of single atoms, and degrades organic matter through an electron transfer mechanism, and no free radicals are generated during the reaction. The electrode degrades organic matter based on an electron transfer mechanism, and no free radicals are generated during the reaction. The electrode has strong resistance to ion interference and strong adaptability to complex water bodies, and can be used for electrochemical treatment of organic matter in sewage and other electrochemical fields.
[0021] Compared with the prior art, the advantages of the present invention are:
[0022] The present invention uses a planar conductive material as a substrate and utilizes the coordination effect between nitrogen atoms in polyvinyl pyrrolidone and Cu to achieve stable loading of Cu single atoms. The entire preparation process mainly includes two steps, pyrolysis and loading, which is simple, efficient, low-cost, and has the potential for large-scale production. No waste is generated after preparation, the raw material utilization rate is high, and the environmental damage is small, which is an environmentally friendly chemical synthesis process.
[0023] The high-efficiency carbon-based catalytic electrode prepared by the present invention not only has the ability to electrochemically catalytically degrade organic pollutants, but also the good electrical conductivity of carbon nanotubes can effectively improve the transfer efficiency of electrons in the catalytic process, so that the performance of the electrode is better than the electrodes currently reported for degrading organic pollutants, and has a good removal effect on various difficult-to-degrade organic pollutants such as dyes, phenols, and antibiotics. In particular, during the reaction, the pollutant electrons are directed to migrate to achieve efficient degradation without additional free radicals, which overcomes the problem that the traditional free radical pathway is easily interfered by coexisting ions in water, and has strong adaptability to complex water quality and wide practicality. In summary, the preparation method of a high-efficiency carbon-based catalytic electrode described in the present invention is simple, low-cost, easy to operate, high catalytic activity, and low metal ion leaching. When the electrode is used for electrochemical degradation of difficult-to-degrade organic matter in water, it is easy to recycle and does not need to add additional powder catalysts to the water body to be treated, which greatly reduces the secondary pollution of the water body and has good practical application prospects.
[0024] The electrode prepared by the present invention can be used for electrochemical reaction to efficiently remove refractory organic pollutants such as dyes, phenols, and antibiotics in water, and the reaction mechanism is an electron transfer pathway without generating additional free radicals. In particular, when the carbon-based electrode is used to remove organic pollutants in water, the removal effect is less interfered by coexisting inorganic ions in water, is easy to separate and recover, and has less metal ion leaching, showing excellent catalytic activity and stability, and can efficiently remove organic pollutants such as bisphenol A in representative surface waters such as Taihu Lake and Poyang Lake, and has good practical application prospects. The electrode provides a new solution for green, efficient, and harmless water treatment strategies. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is the X-ray diffraction spectrum and N2 isothermal adsorption-desorption curve of Cu-CNTs-900@CF;
[0026] Figure 2 is the scanning electron microscope image of Cu-CNTs-900@CF;
[0027] Figure 3 It is the XPS spectrum of Cu and N elements of Cu-CNTs-900@CF;
[0028] Figure 4 The degradation effect diagram of Cu-CNTs-900@CF on 2,4-p-chlorophenol (2,4-DCP), phenol (PE), tetracycline (TC) and bisphenol A (BPA) and the cyclic degradation diagram of bisphenol A are shown;
[0029] Figure 5 are scanning electron microscope images of Cu-CNTs-900@TiF and Cu-CNTs-900@CP;
[0030] Figure 6 This is a graph showing the degradation effects of Cu-CNTs-900@TiF, Cu-CNTs-900@CP and Cu-CNTs-900@CF in removing bisphenol A from water using an electrochemical oxidation device;
[0031] Figure 7 It is the electron paramagnetic resonance spectra of the inhibition and free radical capture of Cu-CNTs-900@CF by different quenchers;
[0032] Figure 8 It is the removal efficiency of Cu-CNTs-900@CF for bisphenol A in typical anionic solution and the removal efficiency of bisphenol A in different surface waters. DETAILED DESCRIPTION
[0033] Embodiment: The present invention is further described in detail below in conjunction with embodiment. It should be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention. If no specific technology or conditions are indicated in the embodiment, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased.
[0034] Example 1: Preparation and application of Cu-CNTs-900@CF
[0035] Dissolve 60 mg of carbon nanotubes, 10 mg of copper chloride and 120 mg of polyvinyl pyrrolidone in 20 mL of ethanol and stir thoroughly to mix them evenly. Then heat it to 75 ° C, and after the ethanol is completely volatilized, collect the remaining mixture. Place the mixture in a porcelain boat, then put it into a tube furnace, and pyrolyze it at 900 ° C in a N2 atmosphere for 2 hours. After cooling to room temperature, wash it with 1 mol / L dilute sulfuric acid for 2 hours, then centrifuge and wash it with deionized water until the pH of the washing liquid is neutral, and obtain Cu-CNTs-900 after centrifugal drying. Then disperse Cu-CNTs-900 in a mixed solution with a volume ratio of 1:1 between water and ethanol, add 0.5% volume fraction of Nation117 solution, and after ultrasonication for 30 minutes, evenly coat it on the conductive carbon felt with a loading of 1 mg / m 2 Then, the mixture was dried at 70°C to obtain the highly efficient carbon-based catalytic electrode Cu-CNTs-900@CF. Figure 1 As shown in the figure, the X-ray diffraction spectrum has two diffraction peaks at 26.2° and 43.2°, which are attributed to the (002) crystal plane and (004) crystal plane of graphite carbon, respectively. The N2 isothermal adsorption-desorption curve shows that the specific surface area of the electrode is 3.05 m 2 / g. Further scanning electron microscope test showed that Figure 2 As shown, carbon nanotube catalysts are distributed on the carbon fibers of the carbon felt substrate, while copper is dispersed on the carbon nanotubes in the form of single atoms. Figure 3 Cu-N bonds appeared in the XPS diffraction pattern, indicating that Cu and N formed a Cu-N coordination structure.
[0036] The high-efficiency carbon-based catalytic electrode of the present invention was used in an electrochemical oxidation device to remove organic pollutants in water. Specifically, a Cu-CNTs-900@CF electrode with a size of 4 cm×6 cm was used to treat bisphenol A in water. 1L of a solution with an organic matter concentration of 5uM was added to the anode, and 40mL of a potassium persulfate solution with a concentration of 2.7g / L was added to the cathode. The results are shown in FIG. Figure 4 As shown in the figure, the removal rate of several organic matters reached 100%. And it can still have good performance after being used ten times, indicating that it has excellent cyclicity. Its reaction mechanism was tested by capture experiment and electron paramagnetic resonance technology. The results are as follows Figure 7 As shown, hydroxyl radicals, sulfate radicals and singlet oxygen scavengers have no effect on the degradation efficiency, and the electron paramagnetic resonance spectrum does not detect the corresponding free radicals, indicating that the electrode does not degrade organic matter through the above-mentioned pathways, but degrades organic matter through the electron transfer pathway.
[0037] In addition, the electrode's ion resistance was tested, and the results showed that Figure 8As shown in the figure, the removal efficiency is almost unaffected in the removal experiments with different anions. The electrode was used to remove the simulated pollutant bisphenol A in actual surface waters such as Taihu Lake, Poyang Lake and Xixi Wetland, with removal rates of 95.01%, 92.71% and 94.67% respectively, indicating that it has application prospects in actual water.
[0038] Example 2: Preparation and application of Cu-CNTs-800@CF
[0039] Dissolve 60 mg of carbon nanotubes, 10 mg of copper chloride and 120 mg of polyvinyl pyrrolidone in 20 mL of ethanol and stir thoroughly to mix them evenly. Then heat it to 75 ° C, and collect the remaining mixture after the ethanol is completely volatilized. Place the mixture in a porcelain boat and then put it into a tube furnace and pyrolyze it at 800 ° C in a N2 atmosphere for 2 hours. After cooling to room temperature, wash it with 1 mol / L dilute sulfuric acid for 2 hours, then centrifuge and wash it with deionized water until the pH of the washing liquid is neutral, and obtain Cu-CNTs-800 after centrifugal drying. Then disperse Cu-CNTs-800 in a mixed solution with a volume ratio of 1:1 between water and ethanol, add 0.5% volume fraction of Nation117 solution, and after ultrasonication for 30 minutes, evenly coat it on the conductive carbon felt with a loading of 1 mg / m 2 Then, the mixture was dried at 70° C. to obtain the highly efficient carbon-based catalytic electrode Cu-CNTs-800@CF.
[0040] The high-efficiency carbon-based catalytic electrode of the present invention is used in an electrochemical oxidation device to remove organic pollutants in water. Specifically, a Cu-CNTs-800@CF electrode with a size of 2cm×3cm is used to treat bisphenol A in water, 60mL of 1.14mg / L bisphenol A solution is added to the anode, and 60mL of 2.7g / L potassium persulfate solution is added to the cathode. The results show that after 45 minutes, the removal rate of bisphenol A reaches 100%.
[0041] Example 3: Preparation and application of Cu-CNTs-900@TiF
[0042] Dissolve 60 mg of carbon nanotubes, 10 mg of copper chloride and 120 mg of polyvinyl pyrrolidone in 20 mL of ethanol and stir thoroughly to mix them evenly. Then heat it to 75 ° C, and after the ethanol is completely volatilized, collect the remaining mixture. Place the mixture in a porcelain boat, then put it into a tube furnace, and pyrolyze it at 900 ° C in a N2 atmosphere for 2 hours. After cooling to room temperature, wash it with 1 mol / L dilute sulfuric acid for 2 hours, then centrifuge and wash it with deionized water until the pH of the washing liquid is neutral, and obtain Cu-CNTs-900 after centrifugal drying. Then disperse Cu-CNTs-900 in a mixed solution with a volume ratio of 1:1 between water and ethanol, add 0.5% volume fraction of Nation117 solution, and after ultrasonication for 30 minutes, evenly coat it on titanium felt with a loading of 1 mg / m 2 Then, the mixture was dried at 70°C to obtain the highly efficient carbon-based catalytic electrode Cu-CNTs-900@TiF. The results of the scanning electron microscope test were as follows: Figure 5 As shown in a, the carbon nanotube precursor is evenly distributed on the titanium fiber.
[0043] The high-efficiency carbon-based catalytic electrode of the present invention was used in an electrochemical oxidation device to remove organic pollutants in water. Specifically, a Cu-CNTs-900@TiF electrode with a size of 2 cm×3 cm was used to treat bisphenol A in water. 60 mL of bisphenol A solution with a concentration of 1.14 mg / L was added to the anode, and 60 mL of potassium persulfate solution with a concentration of 2.7 g / L was added to the cathode. The results are shown in FIG. Figure 6 As shown, after 60 minutes, the removal rate of bisphenol A reached 70%.
[0044] Example 4: Preparation of Cu-CNTs-800@CP
[0045] Dissolve 60 mg of carbon nanotubes, 10 mg of copper chloride and 120 mg of polyvinyl pyrrolidone in 20 mL of ethanol and stir thoroughly to mix them evenly. Then heat it to 75 ° C, and after the ethanol is completely volatilized, collect the remaining mixture. Place the mixture in a porcelain boat, then put it into a tube furnace, and pyrolyze it at 800 ° C in a N2 atmosphere for 2 hours. After cooling to room temperature, wash it with 1 mol / L dilute sulfuric acid for 2 hours, then centrifuge and wash it with deionized water until the pH of the washing liquid is neutral, and obtain Cu-CNTs-800 after centrifugal drying. Then disperse Cu-CNTs-800 in a mixed solution with a volume ratio of 1:1 between water and ethanol, add 0.5% volume fraction of Nation117 solution, and after ultrasonication for 30 minutes, evenly coat it on conductive carbon paper with a loading of 1 mg / m 2 Then, the mixture was dried at 70°C to obtain the highly efficient carbon-based catalytic electrode Cu-CNTs-800@CP. The results of the scanning electron microscope test were as follows: Figure 5 As shown in b, the carbon nanotube precursors are evenly distributed on the carbon fibers.
[0046] The high-efficiency carbon-based catalytic electrode of the present invention was used in an electrochemical oxidation device to remove organic pollutants in water. Specifically, a Cu-CNTs-800@CP electrode with a size of 2 cm×3 cm was used to treat bisphenol A in water. 60 mL of bisphenol A solution with a concentration of 1.14 mg / L was added to the anode, and 60 mL of potassium persulfate solution with a concentration of 2.7 g / L was added to the cathode. The results are shown in FIG. Figure 5 As shown in b, after 60 minutes, the removal rate of bisphenol A reached 55%.
Claims
1. A method for preparing a high-efficiency carbon-based catalytic electrode, characterized in that: The steps include: 1) dissolving carbon nanotubes, polyvinyl pyrrolidone and copper salt in ethanol, mixing and heating to volatilize the ethanol; 2) After the ethanol is completely evaporated, the mixture is placed in a tube furnace, and the mixture is heat-treated in a nitrogen atmosphere. After cooling, the mixture is treated with a dilute acid solution, and then washed with deionized water until the washing water is neutral. After drying, a single-atom catalyst precursor Cu-CNTs based on carbon nanotubes is obtained; 3) The single-atom catalyst precursor Cu-CNTs based on carbon nanotubes is dispersed in a mixed solvent of water and ethanol, and an adhesive is added, ultrasonically dispersed evenly, and then coated on a carbon felt substrate and dried to obtain a high-efficiency carbon-based catalytic electrode.
2. The method for preparing a high-efficiency carbon-based catalytic electrode according to claim 1, characterized in that: In step 1), the carbon nanotubes are single-walled carbon nanotubes, multi-walled carbon nanotubes or graphene; The copper salt is copper chloride, copper nitrate or copper sulfate.
3. The method for preparing a high-efficiency carbon-based catalytic electrode according to claim 1, characterized in that: In step 1), the mass ratio of the copper salt to polyvinyl pyrrolidone is 1-5:24; The mass ratio of the copper salt to the carbon nanotubes is 1-5:
12.
4. The method for preparing a high-efficiency carbon-based catalytic electrode according to claim 1, characterized in that: In step 1), the temperature of the mixed heating is 60-80°C.
5. The method for preparing a high-efficiency carbon-based catalytic electrode according to claim 1, characterized in that: In step 2), the heat treatment temperature is 600-900 degrees Celsius, the heat treatment time is 1.5-4 hours, and the heating rate is 2-10 degrees / minute.
6. The method for preparing a high-efficiency carbon-based catalytic electrode according to claim 1, characterized in that: In step 2), the dilute acid solution is 0.5-1.5 mol / L dilute sulfuric acid or 0.5-1.5 mol / L dilute hydrochloric acid.
7. The method for preparing a high-efficiency carbon-based catalytic electrode according to claim 1, characterized in that: In step 3), the adhesive is Nafion 117, chitosan or conductive adhesive.
8. The method for preparing a high-efficiency carbon-based catalytic electrode according to claim 1, characterized in that: In step 3), the carbon felt substrate is conductive graphite felt, carbon cloth, carbon paper, titanium felt or copper felt.
9. A high-efficiency carbon-based catalytic electrode prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the high-efficiency carbon-based catalytic electrode according to claim 9 in degrading refractory organic pollutants in water during sewage treatment.
Citation Information
Patent Citations
Preparation method of metal matrix composite for carbon nano tube
CN101818280A
CNTs / Cu composite powder and preparation method of CNTs / Cu composite material
CN107326401A
Graphdiyne-carbon nanotube three-dimensional composite material as well as preparation method and application thereof
CN114360917A
Silver modified cuprous oxide electrode for electrocatalytic reduction of CO2 and preparation method of silver modified cuprous oxide electrode
CN115652340A
Carbon nanotube aggregate, and carbon nanotube setting device with the same set therein
JP2004189570A